BIDScoin: A User-Friendly Application to Convert Source Data to Brain Imaging Data Structure - Zwiers, Marcel Peter; Moia, Stefano; Oostenveld, Robert (Frontiers in Neuroinformatics, 2022)
Analyses of brain function and anatomy using shared neuroimaging data is an important development that has acquired the potential to be scaled up with the specification of the new Brain Imaging Data Structure (BIDS) standard. To date, there exists a variety of software tools to help researchers converting their source data to BIDS, but these tools often require programming skills or are tailored to specific institutes, datasets or data formats. Here we introduce BIDScoin, a cross-platform, flexible and user-friendly converter that provides a graphical user interface to help users finding their way in the BIDS standard. BIDScoin does not require programming skills to be set up and used, and supports plugins to extend its functionality. In this paper we show its design and demonstrate how it can be applied to a downloadable tutorial dataset. BIDScoin is distributed as free and open-source software to foster the community driven effort to promote and facilitate the use of the BIDS standard.